2018
DOI: 10.1371/journal.pone.0196987
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and potential activity patterns of planktonic eukaryotic microbes in a mesoeutrophic coastal area (eastern English Channel)

Abstract: The diversity of planktonic eukaryotic microbes was studied at a coastal station of the eastern English Channel (EEC) from March 2011 to July 2015 (77 samples) using high throughput sequencing (454-pyrosequencing and Illumina) of the V2-V3 hypervariable region of the 18S SSU rDNA gene. Similar estimations of OTU relative abundance and taxonomic distribution for the dominant higher taxonomic groups (contributing >1% of the total number of OTUs) were observed with the two methods (Kolmogorov-Smirnov p-value = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
1
9
0
1
Order By: Relevance
“…This novel study characterized the eukaryotic communities in drinking water utilizing also RNA as a template. Activity recovery (RNA–DNA) [20] was considered a more appropriate way to handle this data instead of the RNA/DNA ratio [19, 51, 52] in order to keep also zero values in the analysis. In the relative activity recovery, the scale was limited to lower variation (− 100 to 100), and thus, the distribution of the results was even more extensive than in the RNA/DNA ratio calculation (scale in this data was − 3400- to 14,600-fold).…”
Section: Discussionmentioning
confidence: 99%
“…This novel study characterized the eukaryotic communities in drinking water utilizing also RNA as a template. Activity recovery (RNA–DNA) [20] was considered a more appropriate way to handle this data instead of the RNA/DNA ratio [19, 51, 52] in order to keep also zero values in the analysis. In the relative activity recovery, the scale was limited to lower variation (− 100 to 100), and thus, the distribution of the results was even more extensive than in the RNA/DNA ratio calculation (scale in this data was − 3400- to 14,600-fold).…”
Section: Discussionmentioning
confidence: 99%
“…Significant changes of the RNA: DNA ratio may indicate ecological season events. A recent study have found that the changes of RNA: DNA ratio of Phaeocystis globose , collected at a coastal station of the eastern English Channel, unveiled well to the Phaeocystis bloom dynamic (Rachik et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…Comparison of RNA: DNA ratios usually used in the same species or group among different samples, but not for the comparison between different species or groups (Hu et al, 2016). A previous study showed that the RNA: DNA ratio could be a potential indicator of the upcoming Phaeocystis globosa bloom in the eastern English Chanel (Rachik et al, 2018). Xu et al (2017) observed the varied metabolic activities of protist community at different sampling depths in the South China Sea.…”
Section: Introductionmentioning
confidence: 99%